Detecting the contribution of V5/MT in reading, reading-related tasks, eye-movements and EEG-oscillations in children and adolescents with developmental dyslexia via high-definition tDCS: a protocol study - Somma, Federica; Lazzaro, Giulia; Rima, Samy; Rainich, Kristina; Müller-Axt, Christa; Schmid, Michael Christoph; Vicari, Stefano; von Kriegstein, Katharina; Menghini, Deny (BMC Psychology, 2025)
Background Neuroscientific theories of Developmental Dyslexia (DD) primarily focus on language-related dysfunctions and their associated brain networks. However, DD is also associated with alterations in sensory pathways. For example, there is reduced connectivity in DD, in comparison to controls, between the left lateral geniculate nucleus (LGN) and V5/MT, a motion-sensitive visual area implicated in reading. Most neurostimulation studies in children with DD target language-related brain regions to improve reading, often overlooking motion-sensitive visual areas. Our study aims to target left V5/MT activity using high-definition transcranial Direct Current Stimulation (hd-tDCS) to modulate reading, related processes and physiological mechanisms in children with DD. Methods Using a triple-blind, within-subjects design, 36 children and adolescents (aged 8–13 years) will undergo three conditions: (i) active hd-tDCS over left V5/MT; (ii) active hd-tDCS over V1 (control-site condition); (iii) sham hd-tDCS over left V5/MT or V1 (sham condition). Participants will read a text during each hd-tDCS condition. We will collect data on reading (text, lists of words and nonwords), reading-related processes (visual motion perception, rapid automatized naming of letters and numbers, phoneme blending), and physiological measures (eye movements, EEG-oscillations). Discussion The results of the study could elucidate the role of V5/MT in reading and reading-related processes and demonstrate the neurophysiological effects of V5/MT stimulation. This study may enhance our understanding of how hd-tDCS can induce reading improvement and guide neurobiological-based interventions for children and adolescents with DD. Trial registration The study was registered at ClinicalTrials.gov (ID: NCT05972200) on 8 April 2023.